Probing depth in periodontal pockets: In vitro evaluation of contributions to variability due to probe type and operator skill. (October 2015) - Erriu, Matteo; Genta, Gianfranco; Pili, Francesca Maria Giovanna; Barbato, Giulio; Denotti, Gloria; Levi, Raffaello
Periodontal probing aims at detecting the presence, type and gravity of periodontal diseases influencing distance between gingival margin and connective ligament. Measurements in vivo are affected by substantial uncertainty, owing, for example, to probe features, anatomic variations and operator's skill. Inadequate reproducibility in periodontal probing may lead to diagnostic mistakes and inappropriate therapeutic decisions. In vitro evaluation of reproducibility of measurements of periodontal pockets was aimed at while developing a Periodontal Calibration Box designed to calibrate periodontal probe operators, catering also for simulating contraction observed in vivo. Probe type and clinical experience of operators were found to affect substantially probing errors.